Quantitative, qualitative and located therapeutic experiences with psilocibious fungal microdosis - Valente, Nicolás; Acosta, Luis; Piazza, Nadia; Da col, Jeremías; Pauli Alippi, Tristan; Lavagnino, Nicolás José (Salud, Ciencia y Tecnología - Serie de Conferencias, 2023)
In a context of popularization and boom of the use and research of psychedelic therapies worldwide, the therapeutic use of psilocibious fungi has gained massiveness. Its two main modalities, macrodosis (occasional use of sufficient doses to produce deep perceptual, physiological and psychological effects) and microdosis (use of dose low enough to allow the development of the person in daily activities) are in development, both both in traditional biomedical research such as practices by cultivators, useful networks and organizations linked to health that use or accompany these therapeutics. These developments have shown promising results in the treatment of pathologies mainly linked to mental health. In the present work, we inquire about the therapeutic experiences with microdosis of psilocibious fungi in a group of people who performed, during the year 2022, this therapy in a context of self -arrangement or in accompaniment of alternative health organizations in Argentina. To do this, we conducted an anonymous survey in which the motivations, forms of administration, and perception of benefits and difficulties of therapy were inquired. The survey results indicate that the survey uses use multiple strategies to access, manage and transit therapy, finding relief for medical pathologies for which they approach it, but also improvements in their productivity and benefits linked to non -diagnosed discomforts or to your quality of life in general. This research is the first qualitative systematic registration of therapeutic experiences of users with psilocibious fungi in Argentina and a contribution to value these health practices that work and are made in constant tension with the hegemonic biomedical system and its logics.